The significance of pollen morphology in the taxonomy of the genus Eugenia Linn. (Family: Myrtaceae) - Haron, Noorma Wati; Moore, David M. (Malaysian Journal of Science, 1994)
The pollen grains of Eugenia species from both the Old and New World were examined. They are more or less uniform although slight differences can be detected. In some instances, it is possible to distinguish the grains from the two areas. The width of colpus, exine thickness and exine sculpture may be taxonomically useful in distinguishing the species. Findings of the study show that the of colpus is not a significant taxonomic character in identifying the pollens from the two geographical areas. ABSTRAK Satukajian terhadap debunga spesies-spesies Eugenia dari Dunia Baru dan Dunia Lama telah dijalankan. Walaupun debunga ini hampir serupa, terdapat sedikit perbezaan yang boleh digunakan untuk mengenali debunga dari kedua-dua kawasan tersebut. Lebar kolpus, ketebalan eksin dan rupabentuk eksin mungkin berguna dari segi taksonomi untuk membezakan spesies-spesies berkenaan. Kajian ini menunjukkan struktur kolpus bukanlah ciri taksonomi yang bermakna untuk membezakan debunga Eugenia dari dua kawasan geografi tersebut.